Every day I fight - Scott, Stuart, 1965-2015.; Platt, Larry (New York : Blue Rider Press, 2015)
"A memoir about Scott's fight against cancer"--
Keywords: Scott, Stuart, -- 1965-2015.; Sportscasters -- United States -- Biography; Cancer -- Patients -- United States -- Biography; SPORTS & RECREATION / General; HEALTH & FITNESS / Diseases / Cancer; BIOGRAPHY & AUTOBIOGRAPHY / Sports